Prevalence of Pulmonary Tuberculosis in Indigenous and Non-Indigenous Patients in the State of Zulia, 1996-2005 - Zoila Romero Amaro; Jenny Salazar; Angela Bracho; Ricardo Atencio; Nivia Romero Gori; Ciro Montiel (Kasmera, 2008)
At present, Venezuela is located in the group of countries in the region of the Americas, with a moderate prevalence of tuberculosis, with rates estimated between 25 to 50 cases per 100.000 inhabitants. The high indexes of poverty, unemployment, illiteracy and basic unsatisfied needs occurring in the indigenous population contribute to the increase of tuberculosis cases in the young population. The aim of this investigation was to determine the prevalence of pulmonary tuberculosis in indigenous and non-indigenous patients in the State of Zulia. The study was of the descriptive, retrospective, transversal and non-experimental type, using a total population of 889 cases during the period 1996-2005. The age group with the greater prevalence was 65 to 74 years (15.07%), with 53.65% for males and 40.4% for females. The indigenous population predominated (52.64%) over the non-aboriginal population (47.36%), with the Wayuu ethnic group representing 89.31%. Itwas determined that tuberculosis prevalence has increased over the years, probably due to deficiencies in preventive methods and adapted health promotion programs.